HIV drug resistance and its associated factors among patients during interruption of antiretroviral therapy in China - Zuo, Zhongbao; Huang, Wei; Liu, Lei; Li, Miaomiao; Chen, Hongli; Feng, Yi; Liao, Lingjie; Shao, Yiming; Ruan, Yuhua; Wu, Jing; Xing, Hui (Frontiers in Microbiology, 2025)
BackgroundThe prevalence of human immunodeficiency virus (HIV) drug resistance among people living with HIV (PLWH) who experience treatment interruptions is a significant concern. This study aimed to investigate the prevalence and characteristics of HIV drug resistance for PLWH who experienced treatment interruptions in China.MethodsThis study included 595 PLWH from four studies conducted in China between 2003 and 2021. Data were collected through face-to-face questionnaires, and HIV drug resistance was genotyped using an in-house assay. Multivariate logistic regression analysis was performed to identify factors associated with drug resistance.ResultsThe prevalence of drug resistance was 19.6% (83/424). The most frequent drug resistance mutation was K103N (12.9%). The HIV drug resistance rate and the frequency of patients harboring ≥2 drug resistance mutations decreased significantly in the longer interruption time group. Chi-square trend tests showed that HIV drug resistance, NNRTI drug resistance, K1O3N mutation, and viral load significantly decreased in the longer interruption time group. Multivariate logistic regression analysis revealed that viral load ≥15,000 copies/mL (AOR: 0.58, 95% CI: 0.34–0.98, p = 0.04), interruption time ≥24 months (AOR: 0.29, 95% CI: 0.13–0.63, p = 0.002), and ART duration of 12–24 months before interruption (AOR: 0.36, 95% CI: 0.17–0.76, p = 0.01) were significantly associated with HIV drug resistance.ConclusionThe study found that the prevalence of HIV drug resistance among PLWH who experienced treatment interruptions in China was 19.6%. These findings highlight the importance of conducting drug resistance tests for patients with interruptions before reinitiating ART, especially when the viral load is> 1,000 copies/mL.